Driving After Hallux Valgus Surgery. (September 2017) - McDonald, Elizabeth; Shakked, Rachel; Daniel, Joseph; Pedowitz, David I.; Winters, Brian S.; Reb, Christopher; Lynch, Mary-Katherine; Raikin, Steven M.
Background: The purpose of the study was to determine when patients can safely return to driving after first metatarsal osteotomy for hallux valgus correction. Methods: After institutional review board approval, 60 patients undergoing right first metatarsal osteotomy for hallux valgus correction surgery were recruited prospectively. Patients' brake reaction time (BRT) was tested at 6 weeks and repeated until patients achieved a passing BRT. A control group of twenty healthy patients was used to establish as passing BRT. Patients were given a novel driver readiness survey to complete. Results: At 6 weeks, 51 of the 60 patients (85%) had BRT less than 0.85 seconds and were considered safe to drive. At 6 weeks, the passing group average was 0.64 seconds. At the 8 weeks, 59 patients (100%) of those who completed the study achieved a passing BRT. Patients that failed at 6 weeks had statistically greater visual analog scale (VAS) pain score and diminished first metatarsophalangeal (MTP) range of motion (ROM). On the novel driver readiness survey, 8 of the 9 patients (89%) who did not pass disagreed or strongly disagreed with the statement, "Based on what I think my braking reaction time is, I think that I am ready to drive." Conclusion: Most patients may be informed that they can safely return to driving 8 weeks after right metatarsal osteotomy for hallux valgus correction. Some patients may be eligible to return to driving sooner depending on their VAS, first MTP ROM, and driver readiness survey results. Level of Evidence: Level II, comparative study